Validating a simulation model for laser-induced thermotherapy using MR thermometry - Frank Hübner; Sebastian Blauth; Christian Leithäuser; Roland Schreiner; Norbert Siedow; Thomas J. Vogl (International Journal of Hyperthermia)
Objectives We want to investigate whether temperature measurements obtained from MR thermometry are accurate and reliable enough to aid the development and validation of simulation models for Laser-induced interstitial thermotherapy (LITT).Methods Laser-induced interstitial thermotherapy (LITT) is applied to ex-vivo porcine livers. An artificial blood vessel is used to study the cooling effect of large blood vessels in proximity to the ablation zone. The experimental setting is simulated using a model based on partial differential equations (PDEs) for temperature, radiation, and tissue damage. The simulated temperature distributions are compared to temperature data obtained from MR thermometry.Results The overall agreement between measurement and simulation is good for two of our four test cases, while for the remaining cases drift problems with the thermometry data have been an issue. At higher temperatures local deviations between simulation and measurement occur in close proximity to the laser applicator and the vessel. This suggests that certain aspects of the model may need some refinement.Conclusion Thermometry data is well-suited for aiding the development of simulations models since it shows where refinements are necessary and enables the validation of such models.